Context dependency in interference competition among birds in an endangered woodland ecosystem. (14th February 2023) - Lindenmayer, D. B.; Blanchard, W.; Evans, M. J.; Beggs, R.; Lavery, T.; Florance, D.; Crane, C.; Smith, D.; Siegrist, A.; Lang, E.; Scheele, B. C.
Abstract: Aim: Much research has quantified species responses to human‐modified ecosystems. However, there is limited work on how human‐modified ecosystems may reshape competitive interactions between species. Using a 19‐year study across 3 million ha, we aimed to answer the question: Are levels of interference competition between bird species context dependent and influenced by habitat structure and productivity? We focussed on the hyper‐aggressive behaviour of the Noisy Miner ( Manorina melanocephala ), which is recognized as a key threatening process for other woodland bird species in Australia. Whether environmental conditions such as amount of forest cover and net primary productivity (NPP) mediate the Noisy Miners' impact remains untested at large spatiotemporal scales. Location: Temperate woodlands of south‐eastern Australia. Methods: We gathered data on bird site occupancy from repeated surveys of field sites and assembled satellite data on tree cover and NPP. We constructed Bayesian multi‐species occupancy/detection models of bird species in woodland patches and tested the fixed and interactive effects of Noisy Miner presence, the amount of tree cover, NPP, and time. We quantified the responses of 31 species, many with known interactions with the Noisy Miner documented previously at fine spatial scales. Results: We identified negative associations between the Noisy Miner and 18 bird species, including, unexpectedly, both small and large bodied taxa. Site occupancy in some species was influenced by interactions between Noisy Miner presence and increasing amounts of tree cover or productivity. For some species, interference competition by the Noisy Miner is context‐dependent and mitigated by increasing tree cover and/or increasing NPP. Main Conclusions: Our analyses revealed that woodland bird conservation in our study region will be promoted by protecting refugia characterized by areas of high NPP and high tree cover. Preventing vegetation clearing that reduces tree cover could reduce interference competition by the Noisy Miner on parts of the remaining woodland bird community, including species of conservation concern.